2010
DOI: 10.5187/jast.2010.52.6.481
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Morphology and Behavior of the Sapsaree : A Korean native dog (Canis familiaris)

Abstract: This study was conducted to characterize the morphological and behavior patterns of Sapsaree dogs. The population (n=8,256) has been constructed since 1990 over 12 generations and managed at the Sapsaree Breeding Research Institute, Gyeongsan, Gyeongbuk province. Eighteen morphological and seven behavioral traits were investigated for 882 individuals. Linear models were applied for each trait by fitting sex, season of birth, hair color or test age. The averages of body weight, body length, body height, and dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The tight population bottleneck history in Akita and Bernese mountain dogs was followed by a large reduction in N e ( Rogers and Brace, 1995 ; Wilcox and Walkowicz, 1995 ; AKC, 1998 ) and reflects a long extented LD ( Sutter et al, 2004 ). This result is consistent with the Sapsaree population history, in which significant reduction of the population size occurred during Japanese colonization of Korea more than half a century ago, wherein the breed reached extinction and was re-established about 30 years ago ( Han et al, 2010 ). Moreover, the past N e with significant reduction of the size in recent generations may cause an increasing inbreeding rate in the Sapsaree individuals of the current generation ( Figure 1 ).…”
Section: Discussionsupporting
confidence: 89%
“…The tight population bottleneck history in Akita and Bernese mountain dogs was followed by a large reduction in N e ( Rogers and Brace, 1995 ; Wilcox and Walkowicz, 1995 ; AKC, 1998 ) and reflects a long extented LD ( Sutter et al, 2004 ). This result is consistent with the Sapsaree population history, in which significant reduction of the population size occurred during Japanese colonization of Korea more than half a century ago, wherein the breed reached extinction and was re-established about 30 years ago ( Han et al, 2010 ). Moreover, the past N e with significant reduction of the size in recent generations may cause an increasing inbreeding rate in the Sapsaree individuals of the current generation ( Figure 1 ).…”
Section: Discussionsupporting
confidence: 89%
“…The Sapsaree is a Korean native dog breed with medium body size; long hair is its most prominent feature [ 32 ]. However, individuals with short hair also appear in the population ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Correspondingly, Han et al [22] showed that Sapsarees have greater genetic diversity based on several morphological traits such as tongue spots, dewclaws, tail-set, and coat, nose, and eye color. The Coat color of the Sapsaree also revealed the heterogeneous nature of the breed, indicating two distinct group of blue and yellow including several subdivisions such as blue black, grey black, deep yellow, yellow and light yellow [77].…”
Section: Discussionmentioning
confidence: 99%